Development Strategy and Determinants of it (Economic journal of Lesya Ukrainka Volyn National University, 2016)
The effective strategy of the development depends on the owners and employees. So, the company needs to develop a system of determinants, which transform strategic goals into operational actions of employees. That will allow implementing the strategy which is chosen. In the case, when the variable part of the salary has a large part, it will be very important to identify indicators that reflect the efficiency of labor and how it influences to the efficiency of the enterprise. It is necessary to choose determinates that can provide investors (shareholders, owners) income from the invest capital to the company or to the specific department of the company. Furthermore, they should reflect the positive changes for shareholders, customers and employees in the short and long term in the company activity. Also, such determinates must reflect the growth of the company market value and harmonize the interests of the owners and the management of the company. The strategy of the enterprise and phase of the cycle of the enterprise have effect on the determinates of the enterprise and demand using financial indicators and human capital indicators.
Keywords: balanced scorecard, Skandia Navigator, total shareholder return, weighted averaged cost of capital, free cash flow, economic value added, market value added, cash flow on ROI